2019
DOI: 10.1038/s41598-019-53135-z
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with recombinant enolase of Sporothrix spp. (rSsEno) confers effective protection against sporotrichosis in mice

Abstract: In recent years, research has focused on the immunoreactive components of the Sporothrix schenckii cell wall that can be relevant targets for preventive and therapeutic vaccines against sporotrichosis, an emergent worldwide mycosis. In a previous study, we identified a 47-kDa enolase as an immunodominant antigen in mice vaccinated with an adjuvanted mixture of S. schenckii cell wall proteins. Here, we sought to assess the protective potential of a Sporothrix spp. recombinant enolase (rSsEno) formulated with or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 57 publications
0
14
0
1
Order By: Relevance
“…A vaccine based on peptides of a GP70 antigen showed protection against S. globosa [139] and S. brasiliensis [140]. Another study demonstrated the protective capacity of a vaccine based on recombinant enolase (rSsEno) and Montanide™ Pet Gel A (PGA) as an adjuvant against S. schenckii [141]. However, despite all efforts, there is no immunoprophylaxis or immunotherapy yet available against Sporothrix spp.…”
Section: Vaccine Candidates and Perspectivesmentioning
confidence: 99%
“…A vaccine based on peptides of a GP70 antigen showed protection against S. globosa [139] and S. brasiliensis [140]. Another study demonstrated the protective capacity of a vaccine based on recombinant enolase (rSsEno) and Montanide™ Pet Gel A (PGA) as an adjuvant against S. schenckii [141]. However, despite all efforts, there is no immunoprophylaxis or immunotherapy yet available against Sporothrix spp.…”
Section: Vaccine Candidates and Perspectivesmentioning
confidence: 99%
“…With these initial results, an experimental study to evaluate the effect of the administration of anti-Foxp3 ASO on the immunogenicity of an experimental vaccine against Sporothrix schenckii previously developed in our laboratory [ 27 , 28 ] was carried out. We used the same experimental design previously described but including the anti-Foxp3 ASO within the formulation to determine its effect on the specific immune response.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental vaccine used in this study was designed for the prevention of sporotrichosis, a worldwide emergent subcutaneous mycosis caused by pathogenic species of the genus S. schenckii . The recombinant-Enolase vaccine tested in this study was recently developed by our group and was suggested to be protective against experimental infection in mice [ 27 , 29 ]. Administration of anti-Foxp3 ASO as part of the vaccine formulation induced a considerable upregulation of the Th1-type cytokines IFN-γ and IL-12 in immunized mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As técnicas biotecnológicas também contribuem para obtenção de estrutura biológica nativa de alvos terapêuticos. Em 2019, três importantes estudos revelam proteínas recombinantes como alvos relevantes para desenvolvimento de vacinas preventivas e terapêuticas contra espécies causadoras de esporotricose, criptococose e candidemia (HESTER et al, 2019;PORTUONDO et al, 2019;SINGH et al, 2019).…”
Section: Novas Alternativas No Tratamento E Prevençãounclassified